Predicting the Role of Transformational Leadership on Organizational Citizenship Behavior: Evidence from Airports Employees in the Sorong Area - Taufik Rahman; Kabul Wahyu Utomo; Taufani C. Kurniatun (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The airports in the Sorong area are institutions under the Ministry of Transportation, Directorate General of Civil Aviation. This study aimed to analyze the relationship between transformational leadership and organizational citizenship behavior with the mediating variables of organizational climate and job satisfaction among airports employees in the Sorong area. This research adopted a quantitative approach, using a questionnaire with a Likert scale to collect data. Purposive sampling was utilized to obtain 126 respondents. Furthermore, the data obtained was analyzed using the Partial Least Square Structural Equation Modelling (PLS-SEM). The results concluded that transformational leadership has a positively significant influence on organizational climate and job satisfaction. Organizational climate also had a significant influence on organizational citizenship behavior. However, transformational leadership and job satisfaction had insignificant impact on organizational citizenship behavior. Transformational leadership had a significant indirect impact on organizational citizenship behavior through organizational climate, while job satisfaction did not mediate the relationship between transformational leadership and organizational citizenship behavior. This research examined the influence of transformational leadership on organizational citizenship behavior among airports employees in the Sorong area which are mediated by organizational climate and job satisfaction. Proposed research model was unique in order for gaining a better understanding of organizational citizenship behavior. Research results would help airport leaders in the Sorong area in developing strategies to increase employees organizational citizenship behavior through transformational leadership, organizational climate and job satisfaction.